2018
DOI: 10.3390/polym10060602
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Low Molar Ratio Urea–Formaldehyde Resin with 13C NMR and ESI–MS: Negative Effects of the Post-Added Urea on the Urea–Formaldehyde Polymers

Abstract: Abstract:The structural changes during three-step synthesis of low-molar ratio urea-formaldehyde (UF) resin were tracked by quantitative 13 C nuclear magnetic resonance ( 13 C NMR) analysis and electrospray ionization-mass spectrometry (ESI-MS). Condensations that produced polymers were found to be linked by ether bonds in addition to hydroxymethylation reactions at the first alkaline stage with a formaldehyde to urea ratio of 2:1. Considerable formation of branched methylene linkages, with the highest content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…The crystallization of UF resin exists in both the synthesis process and the curing process [ 15 , 22 ]. Several previous studies have reported the role of linear structural segments in the formation of crystals in UF resins [ 19 , 20 , 26 ]. At the same time, it combines the characterization and analysis results of UF resin before and after curing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystallization of UF resin exists in both the synthesis process and the curing process [ 15 , 22 ]. Several previous studies have reported the role of linear structural segments in the formation of crystals in UF resins [ 19 , 20 , 26 ]. At the same time, it combines the characterization and analysis results of UF resin before and after curing.…”
Section: Resultsmentioning
confidence: 99%
“…As showed in Figure 14 , the growth model of crystals or spherical particles in UF resin is shown. In the synthesis process of urea–formaldehyde resin, the primary microcrystalline particles were formed in the linear molecular chain due to the decrease of solubility in the alkaline stage, and then a stable microcrystalline structure began to form with the adjustment of pH value and the addition of urea [ 19 , 22 , 26 ]. When the UF resin is cured by heating or adding a curing agent (H + ), the colloidal particles aggregate due to the decrease in stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of urea formaldehyde (UF) resin as the adsorbent sample in our laboratory was presented following traditional alkaline‐acid‐alkaline reactions 25 . After this, the obtained sample was cured for 3 h at 120°C to ensure complete dryness.…”
Section: Methodsmentioning
confidence: 99%
“…Decreasing the formaldehyde molar ratio in these resins is among the approaches dedicated for controlling the formaldehyde emission from wood panels. Regrettably, there was a negative impact on the physical and mechanical properties, but even more, the curing rate was slowed down significantly leading to low production line efficiency [20]. Meanwhile, traditional and single curing agents cannot easily solve all the drawbacks of co-condensation resin systems.…”
Section: Introductionmentioning
confidence: 99%